The epidemic of Justinian (AD 542): a prelude to the Middle Ages - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
The epidemic that struck Constantinople and the surrounding countries during the reign of Justinian in the middle of the 6th century, was the first documented pandemic in history. It marked the beginning of plague as a nosological problem that would afflict the world until the 21st century. The symptoms of the disease, as described by various contemporary writers (especially the historian and confidant of the emperor, Procopius, and the two church historians, John of Ephesus and Euagrius), are discussed. There is little doubt that the disease was the plague. The most common form in which it manifested was bubonic plague, which is spread by infected fleas and is not directly contagious from patient to patient. There is also evidence of septicaemic plague and possibly even pneumonic plague. The disastrous effects of the plague were described vividly by contemporary writers. A major problem was to find ways to dispose of infected corpses. It is estimated that about one third of the population died — a figure comparable to the death rate during the Black Death in the Middle Ages. Famine and inflation, the depopulation of the countryside, and a critical manpower shortage in the army were further effects which all contributed to bringing to a premature end Justinian’s attempt to restore the grandeur of the Roman empire, and precipitating the advent of the Middle Ages.